ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.N DI WILAYAH PUSKESMAS PEKAUMAN BANJARMASIN - Nur Cahyani Ari Lestari; Ainun Hudiyah Marpuah (Universitas Batam, 2023)
According to the Indonesian Demographic and Health Survey (IDHS) 2017, the Maternal Mortality Rate (MMR) related to pregnancy, childbirth and the postpartum period is 265 per 100,000 live births, while the infant mortality rate is 27 per 1,000 live births. Number of live and active babies born. In reducing MMR and IMR, as well as preventing complications in pregnancy and childbirth, early detection of high risk is very necessary with the support of quality services and other events such as counseling, classes for pregnant women and comprehensive care. Objective: To carry out comprehensive midwifery care for Mrs. H from pregnancy to family planning. Research method: This research is a case study by understanding the condition of the client and the problems faced by Mrs. P 22 years G1P0A0 UK 33 weeks, conducted in October 2020-January 2021, data collection namely observation, interviews, measurements and documentation using a case study instrument in the form of the SOAP midwifery care format. Results: Based on the assessment during pregnancy, Mrs. P is normal and has no complaints. Evaluation of the client in good and normal condition. Smooth delivery. The baby was born normal, during the visit no problems were found. Uterine involution is normal and there are no complaints. KB care for Mrs. P plans to take lactation pills. The care provided is in accordance with the standard of care